Stronger together: Positive relationships at work - Grabarski, M. K.; Schneider, N.; Yadav, M.; Spreitzer, G. M.; Dello Russo, S.; Wang, K.; Wurtz, O.; Dimitrova, M.; Lazarova, M. B.; Legood, A.; Mirfakhar, A.; Mouratidou, M.; et al. (Academy of Management Annual Meeting Proceedings, 2022, 2022)
The workplace in the 21st century has changed dramatically, as the internet connected the world, the “gig economy” changed work arrangements, globalization expanded the job market and individual work values such as autonomy and freedom became dominant (Rabenu, 2021). Just a few years ago, automation and technology were the heart of the conversation on the modern workplace and seemed to be replacing meaningful human connections. However, the COVID-19 pandemic, that required social distancing, demonstrated just how much people still need each other, and how technology cannot replace human relationships. The Positive Organizational Scholarship (POS) movement that started in the early 2000’s seeks to understand the role of positive relationships at work. The place of work in our lives makes it a source of meaning, purpose and identity-building, that are often created through positive relationships (Ragins & Dutton, 2007). For example, high-quality relationships enable human flourishing that in turn benefits the organization (Dutton & Heaphy, 2003). Another notable outcome of the movement is the Reflected Best Self Exercise (Quinn, Dutton, Spreitzer, & Roberts, 2003) that helps understand individual strengths through feedback from significant others. The purpose of this symposium is to contribute to understanding the role of positive relationships in the workplace. This collection of papers explores different types of work relationships with leaders, coworkers and work friends to examine how positive emotional connections help overcome challenges and promote well-being. By looking at processes on different levels of analysis, this symposium offers a broader perspective on workplace relations and unique roles they can play for employees and for organizations.